The potential competitive impact of the climate change indicator Montagu’s crab (Xantho hydrophilus Herbst, 1790) on juvenile edible crab (Cancer pagurus Linnaeus, 1758) - JOSEPH DOWLING (2022)
Climate change is driving distribution shifts globally, and these shifting species can be considered indicators for the environment. The northward range expansion of Montagu’s crab Xantho hydrophilus, a shift recently observed along the southeast coast of the UK, has earned this Lusitanian xanthid the climate change indicator tag. X. hydrophilus densely populates rocky, boulder-rich shores, in which it likely competes with other intertidal animals. Of those, other crabs occupying an overlapping niche are likely to be X. hydrophilus’ most significant competitors, including the commercially important edible crab C. pagurus. In this study, laboratory experiments testing interference competition for refuge and prey between adult X. hydrophilus and juvenile C. pagurus were conducted through multiple trial treatments, which incorporated various species, size and density combinations. By running these trials, I sought to test my hypotheses that the more robust X. hydrophilus would outcompete, overpower and displace C. pagurus. Interspecific concurrence interfered with foraging for both species, however X. hydrophilus dominated size-matched C. pagurus in agonistic interactions, and were only matched by considerably size-advantaged C. pagurus. X. hydrophilus were also overwhelmingly dominant at refuge retention and displacement versus C. pagurus, yet more tolerant of cohabitation, particularly with conspecifics. In contrast, C. pagurus were hyperaggressive versus conspecifics yet more passive and subordinate to X. hydrophilus, which was evident in both foraging and refuge trials. This study suggests that X. hydrophilus is not only a superior competitor to juvenile C. pagurus, but could potentially saturate rocky shore refuge due to high degrees of refuge dependency and conspecific tolerance. This could result in the exclusion of C. pagurus from its nursery habitat, culminating in population bottlenecks. However, the poorly understood X. hydrophilus requires further research in order to substantiate the conclusions of this study and impel consideration for active population monitoring.